Peran Nilai Tanggung Jawab dan Kepemilikan Moral dalam Mewujudkan Kepemimpinan Etis Berbasis Etika Bisnis Islam pada UMKM - Suprapto, Helman; Bustaram, Isnain; Sayyidi, Sayyidi; Mabruroh, Hajjatul; Salim, Abd (Assyarikah: Journal of Islamic Economic Business, 2025)
This study aims to examine the effect of sense of responsibility on ethical leadership through the mediating role of moral ownership among Micro, Small, and Medium Enterprise (MSME) managers in Pamekasan Regency. A quantitative approach was employed using Partial Least Square Structural Equation Modeling (PLS-SEM) to analyze data collected from 100 respondents. The results reveal that sense of responsibility significantly influences moral ownership, which in turn mediates its effect on ethical leadership. Theoretically, the findings strengthen the value-based leadership model in the MSME context. Practically, the results provide an initial foundation for fostering ethical leadership development in the MSME sector.